Standardized 10‐step approach for successfully performing a hysterectomy via vaginal natural orifice transluminal endoscopic surgery. (22nd April 2022) - Housmans, Susanne; Stuart, Andrea; Bosteels, Jan; Deprest, Jan; Baekelandt, Jan
Abstract: Vaginal natural orifice transluminal endoscopic surgery (NOTES) is a novel technique for minimally invasive gynecological surgery. Adequate training and standardization are key elements to patient safety and quality of care. Based on consensus statements and expert opinion; we report a step‐by‐step guidance for hysterectomy via natural orifice transluminal endoscopy. A detailed description is presented of pre‐ and postoperative care, and the instruments and equipment used, and surgical steps are illustrated by photographic images. This report can guide surgeons in their training to perform a hysterectomy via NOTES.